Mixed Type Duality for Set-valued Optimization Problems via Higher-order Radial Epiderivatives. (2nd July 2016) - Anh, Nguyen Le Hoang
ABSTRACT: In this article, we introduce a notion of higher-order radial epiderivative for set-valued maps and study its properties. A generalized concept of higher-order strict minimizers in set-valued optimization is proposed as well. By virtue of the radial epiderivative, we establish a mixed dual problem, and then weak, strong, and converse duality theorems are obtained in dealing with generalized strict minimizers.